Contaminant Investigations of Regularly used Eye Contact Lenses - Rebwar Muhammad Hamasalih; Karzan Abdulmuhsin Mohammed; Pinar Khalid Khudhur (Institute of Medico-legal Publications Pvt Ltd, 2021)
Microorganisms, particularly bacteria, are considered to play a role in the etiology of certain corneal infectionsobserved during soft contact lens wear. This study explored the possibility of microbial colonization of softcontact lenses as a risk factor leading to corneal infection. In a clinical trial conducted and 86 lenses wererecovered aseptically and analyzed for microbial colonization. The incidence of bacteria and fungi wasfewer during corneal infection than during asymptomatic lens wear. During asymptomatic lens wear, cornealinfection bacteria were isolated most frequently and were usually normal external ocular microbiota. Of theGram-positive bacteria, the incidence of Staphylococcus aureus was fewer during asymptomatic wear. WhileGram-negative bacteria were seen in high cases during asymptomatic wear, this includes Escherichia coliand Pseudomonas aeruginosa. Fungal screening and identification revealed 2 cases of contamination withthe yeast Candida albicans that able to form a biofilm. Colonization of soft contact lenses with pathogenicbacteria, especially gram-negative and gram-positive bacteria, appears to be a significant risk factor leadingto corneal infection.